The triangular relationship between energy consumption, trade openness and economic growth: new empirical evidence - Mandella Osei Assibey Bonsu; Ying Wang (Cogent Economics & Finance, 2022)
Our paper examines the triangular relationships between energy consumption, trade openness and economic growth of 45 countries from 1991 to 2014 using dynamic seemingly unrelated regression (DSUR) models. We confirm a bidirectional relationship among energy consumption and income, trade openness and income, trade openness and energy consumption for countries in the long run. Interestingly, the impact of energy consumption on economic growth is larger than the impact of trade openness, trade openness evidence larger impact on energy consumption than the impact of economic growth. However, the effect of economic growth on trade openness is the largest in the triangular relationships. We suggest that energy measures that aim to lessen energy usage in an economy will hinder economic growth. Our results provide insights for policymakers to understand and develop energy, trade, and environmental policies for sustainable development in the long run.
Keywords: F14; O13; Q43; Q48; 330; DSUR model; economic growth; energy consumption; international trade